Sistem Informasi Pengajuan Desa Untuk Bantuan Rumah Tidak Layak Huni - Khilmi, Wildan; Sumarno, Sumarno (Journal of Information System Research (JOSH), 2025)
The Uninhabitable Housing Assistance Program (RTLH) aims to help underprivileged people obtain adequate housing. However, in the process, there are still various obstacles, such as ineffective administration, limited access to information, and data verification that takes a long time. Therefore, this research focuses on developing a Village Information and Submission System to support the Housing and Settlement Service in managing aid more optimally. The method used in developing this system is the Software Development Life Cycle (SDLC), which includes the stages of planning, analysis, design, implementation, testing and maintenance. The results obtained show that the system developed is able to speed up the application process, increase information transparency, and assist the government in verifying and distributing aid more efficiently and on target, This research is expected to provide benefits for the Village Information System and Submission for Uninhabitable House Assistance from the Housing and Settlement Service. and assist the Submission of Assistance Recipients in improving housing standards in.